KEPEMIMPINAN ORGANISASI MAHASISWA DALAM MENGHADAPI TANTANGAN REGENERASI DAN KEBERLANJUTAN PROGRAM: STUDI KASUS PADA WP2SOSPOL UNIVERSITAS NEGERI PADANG - Rifki Kurniawan; Syamsir Syamsir; Muhammad Haikal Faiz; Rahmat Aidil Fitrialdi; Rianda Manorangi Irawan; Syawal Irfan Hakim (STKIP Subang, 2026)
Leadership is one of the key determinants of student organization sustainability, particularly in managing leadership regeneration and maintaining the continuity of work programs across successive management periods. This study aims to examine the role of student organization leadership in addressing regeneration challenges and sustaining program continuity, using WP2SOSPOL at Universitas Negeri Padang as a case study. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews with organizational administrators who had direct experience in leadership and cadre development processes, then analyzedthrough data reduction, data display, and conclusion drawing, with validity ensured through source and technique triangulation. The findings indicate that WP2SOSPOL applies a hierarchical yet democratic leadership system, supported by a multi-level cadre development scheme ranging from member orientation to advanced leadership training. The most prominent regeneration challenge is the low psychological readiness of cadres to assume leadership positions, while program sustainability is strongly influenced by communication effectiveness, consistent tiered evaluation, and the role of the Advisory Board in bridging knowledge across leadership generations. The study concludes that the success of regeneration and program sustainability in student organizations largely depends on the leader's capacity to build a structured cadre system and a continuous culture of evaluation.